Internet of Things (IoT): Readme - Istabraq M. Al-Joboury; Emad H. Al-Hemiary (QALAAI ZANIST JOURNAL, 2021)
Internet of Things (IoT) integrates billions of the heterogeneous IoT things with the Internet in which the embedded systems such as sensors and actuators linked together to improve quality of life, and becomes the future of technologies in any field of human daily life. These IoT devices cooperate with each other and generate useful information to provide better services and applications to the governments and the society. Also, there is a need to store these data on Cloud for monitoring. This paper, surveys IoT applications, new challenges and issues arise in different fields and provides IoT architecture, focuses on explanation of IoT protocols and their operations and functionalities, presents different microcontroller types used by researchers. With the huge amount of data generated from IoT devices, the integrating Cloud and IoT may helpful, Therefore, a survey on open issues faced when these two concepts integrating together is discussed. The objective of this paper is to provide a survey for everything related to IoT and direct it to all beginners in this filed or academic researchers.